The persistence of component Theileria parva stocks in cattle immunized with the ‘Muguga cocktail’ live vaccine against East Coast fever in Uganda - Oura, C.A.L.; Bishop, Richard P.; Wampande, E.M.; Lubega, G.W.; Tait, A. (Cambridge University Press, 2004)
The "Muguga cocktail" live vaccine comprises three Theileria parva stocks (Muguga, Kiambu 5 and the buffalo-derived Serengeti-transformed) and has been used extensively in Eastern, Central and Southern Africa with an infection and treatment protocol to protect cattle against East Coast fever. We report the characterization of the three component vaccine stocks using a panel of polymorphic micro-satellite and mini-satellite markers and the development of a stock-derived PCR method that distinguishes two of the vaccine stocks. These markers, with the use of a recently developed Reverse Line Blot assay, have enabled us to address four important questions in relation to vaccination. First, how closely related are the vaccine stocks, secondly do all three stocks persist post-vaccination and induce a carrier state, thirdly is there evidence for the transmission of the vaccine stocks and fourthly does vaccination prevent infection with local genotypes? The results show that Muguga and Serengeti-transformed stocks are highly related but very distinct from Kiambu 5 that persists in vaccinated cattle establishing a carrier state. No evidence was obtained for the transmission of vaccine stocks to co-grazed animals, although these animals were infected with up to 8 different T. parva genotypes showing there was a significant level of tick challenge. Some of the vaccinated animals become infected with a subset of local genotypes providing evidence for limited vaccine "breakthrough".